2010
DOI: 10.3109/02688697.2010.487129
|View full text |Cite
|
Sign up to set email alerts
|

Giant erosive spinal schwannomas: surgical management

Abstract: Giant erosive spinal schwannomas can be distinguished from other spinal schwannomas by its growth in myofascial planes and vertebral body erosion. Therapeutic radical tumour excision without neurologic deterioration is possible in the management. Prognosis is good after total tumour removal. In this article, it is aimed to report six patients who were diagnosed as giant erosive spinal schwannomas between 2001 and 2004 according to the criteria of Sridhar et al. Three of the patients were male and three female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Giant invasive spinal schwannomas may be encountered most frequently in the cervical spine [16] or lumbosacral and sacral spine [5,6]. In the present review of pediatric cases, the lumbar spine was most commonly affected (two cases), followed by the lumbosacral spine (one case), and thoracic spine (one case).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Giant invasive spinal schwannomas may be encountered most frequently in the cervical spine [16] or lumbosacral and sacral spine [5,6]. In the present review of pediatric cases, the lumbar spine was most commonly affected (two cases), followed by the lumbosacral spine (one case), and thoracic spine (one case).…”
Section: Discussionmentioning
confidence: 80%
“…The optimal surgical strategy for giant invasive spinal schwannomas involves decompression of the spinal cord and gross total resection, while preserving nearby neurovascular structures and addressing the potential for vertebral column instability. Reports on the clinical features of giant invasive spinal schwannomas and treatment approaches based on outcome are sparse [14-16]. Moreover, to the best of our knowledge, there have only been three previous descriptions of the clinical features of these tumor and surgical strategies in children [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the reported case presentations and case series were comprised of sacral GSS, a review of the related literature revealed that many GSS cases are located in the lumbar spine; indeed, 60-70% of GSSs have been reported to be lumbar by other studies 10,13-18. High rates of cervical GSSs have only been reported by Kim et al19 and Özdemir et al,14 who found rates of 50-55% in their series. In our series, most of the GSSs were located in the lumbosacral area (11 cases; 61.1%).…”
Section: Discussionmentioning
confidence: 95%
“…Perhaps the follow-up time (mean 1.9 years) was relatively shorter. Additionally, some authors prefer aggressive tumor management for sacral schwannoma via wide resection and total sacrectomy given the risk of local recurrence [1719]. But this debated strategy often results in sacral nerve dysfunction and more blood loss.…”
Section: Discussionmentioning
confidence: 99%